2018
DOI: 10.1111/ggi.13565
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of getting out of bed in patients with Alzheimer's disease monitored by non‐wearable actigraphy

Abstract: Aim Sleep disturbances in patients with Alzheimer's disease have not been systematically evaluated, because sleep monitoring has proved difficult. Our goal was to quantitatively characterize sleep disturbances in patients with Alzheimer's disease. Methods The present study was a cross‐sectional descriptive study, carried out in dementia care units in Japan. Participants were 63 patients with Alzheimer's disease (mean age 77.6 ± 8.0 years) with severe behavioral and psychological symptoms of dementia. A non‐wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…Moreover, AD patients showed a higher prevalence of other alterations in actigraphic parameters, thus confirming that the evolution of cognitive impairment is associated with a reduction in sleep quality. The increase in the number of NA in cognitive impairment patients, besides underlining the relevance of actigraphy in detecting and defining the extent of motor hyperactivity [32], further emphasizes that sleep deprivation is a common feature in patients with dementia [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AD patients showed a higher prevalence of other alterations in actigraphic parameters, thus confirming that the evolution of cognitive impairment is associated with a reduction in sleep quality. The increase in the number of NA in cognitive impairment patients, besides underlining the relevance of actigraphy in detecting and defining the extent of motor hyperactivity [32], further emphasizes that sleep deprivation is a common feature in patients with dementia [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, previous studies on STS measurements primarily used video recordings to evaluate postures or motion sequences and no sensor-based studies have ever been conducted in patients with PD. One recent study used non-wearable actigraphy placed under patient mattresses to determine the number of waking events and number of times patients with Alzheimer's disease left their beds ( 31 ). While a high frequency of getting out of bed was demonstrated in this study, it was not possible to capture axial and limb muscle movement patterns with non-wearable devices.…”
Section: Discussionmentioning
confidence: 99%
“…Although subjective sleep status might predict nighttime care needs, it is also necessary to objectively clarify CRs' sleep status. 26 Home-based care is becoming increasingly critical in Japan; therefore, it is meaningful to determine how to reduce objective care burden among FCs. 27 Our results indicated that reduced objective total sleep time (as measured by the ActiGraph) is significantly associated with FCs' care burden severity.…”
Section: Discussionmentioning
confidence: 99%